Anti‐monoclonal antibody treatment during pregnancy and lactation in women with multiple sclerosis or neuromyelitis optica spectrum disorder. Issue 3 (22nd August 2022) - Nohara, Chiyoko
Abstract: Multiple sclerosis (MS) and neuromyelitis optica (NMOSD) are more prevalent in women and mainly affecting young women, the majority of whom are of childbearing age. In addition, recent treatment algorithms suggest that patients who have poor prognostic factors are treated with highly effective disease‐modifying drugs from the beginning. Anti‐monoclonal antibodies for MS or NMOSD are basically highly effective disease‐modifying drugs. Therefore, young women with MS or NMOSD will have more opportunities to receive anti‐monoclonal antibody treatment than ever before. Currently, five anti‐monoclonal antibodies for MS or NMOSD are available in Japan: natalizumab and ofatumumab for MS, and eculizumab, satralizumab and inebilizumab for NMOSD. The pregnancy and breastfeeding of each anti‐monoclonal antibody drug is reviewed, and the evidence surrounding the safety of anti‐monoclonal antibody drugs during both pregnancy and breastfeeding in women with MS or NMOSD is discussed.